Environmental sustainability: The intersection of agrifood systems with ecosystem health - Ringler, Claudia; Zhang, Wei; Nkonya, Ephraim M.; Wyckhuys, Kris A.G.; Rakotonarivo, O. Sarobidy; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2025)
Climate change and biodiversity loss are arguably the greatest environmental challenges facing humanity today, and unsustainable agrifood systems are both a key cause and consequence of this environmental degradation. This chapter reviews how key environmental challenges in land, water, and energy systems intersect with agrifood systems and describes research contributions toward understanding and addressing these challenges over the past 50 years, as well as exploring future directions for environmental sustainability research.